Julius Africanus und die christliche Weltchronistik - Wallraff, Martin 1966-; Iulius Africanus, Sextus 160-240 (Berlin New York Walter De Gruyter, 2012)
Biographical note: Martin Wallraff, Universität Basel, Schweiz.
Julius Africanus (3. Jh.) ist als „Vater der christlichen Chronographie0 bezeichnet worden; darunter versteht man die genaue Berechnung von Zeiten (etwa die Datierung der Inkarnation, indirekt auch des Weltendes). Zugleich finden sich bei ihm aber auch die Anfänge christlicher Universalgeschichte (Weltchronistik), einer Gattung, die über Jahrhunderte das Geschichtsdenken des Abend- und Morgenlandes maßgeblich bestimmt hat. Die vorliegenden Studien erschließen diese zum Teil schwer zugängliche Literatur und leisten wesentliche Forschungsbeiträge zur lateinischen, griechischen und orientalischen Weltchronistik.
Julius Africanus (3rd cent.) has been called the 0Father of Christian Chronography0– the exact calculation of dates and ages (such as the date of the Incarnation, and indirectly also of the end of the world). At the same time, however, he also presents the beginnings of a Christian universal history (Universal Chronicle), a genre which decisively influenced the historical thinking of both Orient and Occident over hundreds of years. The present studies open up this literature– some of which is virtually inaccessible– and make significant contributions to research into Latin, Greek and Oriental representations of the genre of universal chronicle.
Review text: "Insgesamt ist der vorliegende Tagungsband äußerst lesenswert."Alexander Weiß in: http://hsozkult.geschichte.hu-berlin.de/rezensionen/2008-2-053
Contains bibliographic information and indexes
International conference proceedings
Online-Ausgabe
In German
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Africanus, Sextus Julius -- Congresses; Africanus, Sextus Julius -- Congresses; Chronology, Historical -- Congresses; History, Ancient -- Chronology -- Congresses; Chronology, Historical; History, Ancient; Historiography -- Chronicle -- Julius Africanus; HISTORY / Ancient / Rome; Chronicle; Julius Africanus; historiography; Konferenzschrift -- 2005 -- Eisenach